THE ROLE OF WILD BIRDS IN PRESERVATION AND PREVALENCE OF AVIAN PARAMYXOVIRUS SEROTYPE 1 (NEWCASTLE DISEASE VIRUSES) IN SIBERIA AND THE FAR EAST, RUSSIA - A. V. Glushchenko; K. S. Yurchenko; A. K. Yurlov; Yu. G. Yushkov; M. Yu. Shchelkanov; A. M. Shestopalov (Юг России: экология, развитие)
The aim is to evaluate ecological diversity of wild birds in Siberia and the Russian Far East, which are carriers of Newcastle disease virus that belongs to potentially dangerous pathogen for poultry.Methods. Biological materials (cloacal swabs and intestinal fragments) of wild migratory birds were collected in 2008-2014. The viral isolates were propagated in the allantoic cavity of developing chicken embryos. The presence of virus was determined in hemagglutination tests and primary identification of Newcastle disease virus was confirmed by RT-PCR. Pathogenicity of the obtained isolates was determined in tests ICPI and MDT.Results. 4443 samples were obtained from wild migratory birds of 11 avian orders and were investigated. Newcastle disease virus was detected in 40 birds from 4 orders. The Duck family (Anatidae) of the Waterfowl order (Anseriformes) plays the leading role in the circulation of Newcastle disease virus in Siberia and the Far East.The main species among them - a teal (Anas crecca), a garganey (Anas querquedula), a mallard (Anas platyrhynchos) and a shoveler (Anas clypeata). All studied isolatesof Newcastle disease virus are apatogenic except for two deponated strains.Main conclusions. Wild migratory birds from orders Anseriformes and Charadriiformes are capable of carrying Newcastle diseasevirus and could transfer pathogenic variants of this virus to the Russian territory.